Proposed pathways for moving forward - Piñeiro, Martin; Piñeiro, Valeria (International Food Policy Research Institute, 2024)
In Chapter I, the introduction of this book, we present a succinct description of the many difficulties that the World Trade Organization (WTO) and its member countries have encountered over the last decade in their attempts to advance in negotiations toward agreements that could contribute to more open and transparent global trade and the discussions taking place as a result of these difficulties. Starting from this context, the rest of the book aims to contribute to three important themes that have emerged from recent discussions in the WTO. The selection of these themes and the authors’ proposals to solve these themes are influenced by the needs and perspectives of Latin America, specifically the region’s food-exporting countries.